ANALISIS MOTIVASI BELAJAR DALAM PEMBELAJARAN EKONOMI DI KELAS X SMA SANTO FRANSISKUS ASISI PONTIANAK - Hendrik, Matius; Kosmas, , F. Y; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis is "Analysis Motivation to learn Economic Learning in Class X Social Sciences SMA St. Francis Assisi Pontianak". A common problem in this thesis is "to describe the learning motivation of students in class X economic learning at Santo Fransiskis Asisi High School in Pontianak. The sub-problems are, how the interest in learning class X students, how the desire to study class X students, how the ego involvement of class X students, what forms of positive punishment given by the teacher to class X students, how to reward prizes by teachers to class X students, how praise is given by the teacher to class X students. The data collection tool used in this thesis is an interview guide, field notebook, checklist, questionnaire. The analysis in this thesis was presented in a qualitative descriptive manner using information from economic subject teachers totaling 1 person who taught at Santo Franciscan Asisi Pontianak High School and filled out questionnaires conducted by class X students totaling 30 students. The results of this study indicate that motivation in students is not fully owned by students of class X IPS of St. Francis of Assisi and only 27 have interest, 20 have passion, 22 have Ego Involvement. while the provision of extrinsic motivation, namely economic subject teachers can also be said not to be fully carried out by the economics teacher of class X IPS of St. Francis Asisi High School for example giving praise and prizes to active students and their grades completed above the average have not been carried out fully in accordance with the given motivation indicators by the teacher..Â Keywords: Motivation To Learn In Economic Learning